Information Leakage and Market Efficiency - Brunnermeier, Markus K. (Review of Financial Studies, 2005)
This article analyzes the effects of information leakage on trading behavior and market efficiency. A trader who receives a noisy signal about a forthcoming public announcement can exploit it twice. First, when he receives it, and second, after the public announcement since he knows best the extent to which his information is already reflected in the pre-announcement price. Given his information he expects the price to overshoot and intends to partially revert his trade. While information leakage makes the price process more informative in the short-run, it reduces its informative-ness in the long-run. The analysis supports Securities and Exchange Commission’s Regulation Fair Disclosure. In a perfect world, all investors would receive information pertinent to the value of the stock immediately and simultaneously. In reality, however, some agents like corporate insiders and their favored analysts can receive signals about this information before it is disclosed to the general public. The focus of our analysis is to determine (i) the optimal trading strategy of an early-informed agent and (ii) the implications of this trading behavior